2012
DOI: 10.1016/j.jtcvs.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Serial multidetector computed tomography assessment of left ventricular reverse remodeling, mass, and regional wall stress after restrictive mitral annuloplasty in dilated cardiomyopathy

Abstract: Our findings indicate that ventricular reverse remodeling occurs soon after restrictive mitral annuloplasty. In contrast, myocardial reverse remodeling (ie, regression of myocardial hypertrophy) occurs over time between the early and late postoperative periods. Our data also suggest that the late improvement in left ventricular systolic performance might be attributable to a decrease in the left ventricular afterload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…13 It provides excellent temporal and spatial resolution, it is very accurate, and it facilitates reproducible quantitative measurements of cardiac structure and function. 20 In our study, cardiac MRI illustrated post infarction, eccentric adverse ventricular remodeling in both cell sheet-treated and untreated negative control groups. However, EPC-SMC cell sheet transplantation significantly enhanced ventricular function and attenuated ventricular remodeling compared with that of untreated controls.…”
Section: Discussionsupporting
confidence: 50%
“…13 It provides excellent temporal and spatial resolution, it is very accurate, and it facilitates reproducible quantitative measurements of cardiac structure and function. 20 In our study, cardiac MRI illustrated post infarction, eccentric adverse ventricular remodeling in both cell sheet-treated and untreated negative control groups. However, EPC-SMC cell sheet transplantation significantly enhanced ventricular function and attenuated ventricular remodeling compared with that of untreated controls.…”
Section: Discussionsupporting
confidence: 50%
“…LV remodeling is usually assessed using echocardiography 10,11,12 but has also been assessed using single-photon computed tomography (SPECT) and CMR 20 . Computed tomography (CT) is another modality to assess serial LV volumes 21 . Although assessment of LV volumes by SPECT and CT are highly reproducible, they utilize ionized radiation.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 64-slice CT more accurately evaluated left ventricle function than ventriculography or echocardiography. Other researchers also showed that CT was useful in evaluating the function of the left ventricle in patients with cardiomyopathy or valvular disease (206, 207, 208), and reported on the feasibility using CT in the evaluation of the diastolic function of the left ventricle (209). However, the use of CT is restricted by radiation exposure and the use of contrast agents.…”
Section: Prefacementioning
confidence: 99%